Konstruksi Patriotisme Anak Berdasarkan Yeremia 29:7: Studi Kasus pada Siswa Kristen Kelas 3–6 di Kecamatan Tingkir, Kota Salatiga - Gersom Kurniawan; Ruwi Hastuti; Ribut Agung Sutrisno (Sekolah Tinggi Teologi Kanaan Nusantara, 2025)
This study aims to construct the understanding and practice of patriotism among Christian children based on Jeremiah 29:7, which emphasizes the importance of seeking and praying for the welfare of the city. Using a qualitative case study approach, the research involved Christian students in grades 3–6 and Christian Religious Education teachers in Tingkir District, Salatiga City, selected purposively. The results show that students’ understanding of patriotism is beginning to develop, marked by love for the homeland, respect for national symbols, and pride in being Indonesian citizens. The implementation of these values is reflected in concrete activities such as flag ceremonies, maintaining cleanliness, living in harmony, and praying for the nation. Teachers play an active role in integrating these values into Christian Religious Education using a contextual faith-based approach. The novelty of this study lies in the integration of patriotism with the theological foundation of Jeremiah 29:7, which highlights the spirituality of prayer and children’s involvement in the nation’s welfare, as well as its application in Christian religious education at the elementary school level through a contextual faith-based approach. In conclusion, children’s patriotism can be meaningfully nurtured through the integration of spiritual and national values in Christian education.AbstrakPenelitian ini bertujuan mengkonstruksi pemahaman dan praktik patriotisme anak Kristen berdasarkan Yeremia 29:7, yang menekankan pentingnya mengusahakan dan mendoakan kesejahteraan kota. Menggunakan pendekatan kualitatif studi kasus, penelitian melibatkan siswa Kristen kelas 3–6 dan guru PAK di Kecamatan Tingkir, Kota Salatiga, yang dipilih secara purposive. Hasil menunjukkan bahwa pemahaman siswa tentang patriotisme mulai terbentuk, ditandai dengan rasa cinta tanah air, menghormati simbol negara, dan bangga menjadi warga Indonesia. Implementasi nilai ini tampak melalui kegiatan nyata seperti upacara bendera, menjaga kebersihan, hidup rukun, dan doa untuk bangsa. Guru berperan aktif mengintegrasikan nilai-nilai ini dalam pembelajaran PAK dengan pendekatan kontekstual berbasis iman. Kebaruan penelitian ini terletak pada integrasi nilai patriotisme dengan dasar teologis Yeremia 29:7, yang menekankan spiritualitas doa dan keterlibatan anak dalam kesejahteraan bangsa, serta penerapannya pada pendidikan agama Kristen di tingkat sekolah dasar dengan pendekatan kontekstual berbasis iman. Kesimpulannya, patriotisme anak dapat ditumbuhkan secara bermakna melalui integrasi nilai spiritual dan kebangsaan dalam pendidikan agama Kristen.